Relative ecological fitness of glyphosate-resistant kochia from western Kansas - Osipitan, Omobolanle Adewale (Kansas State University, 2016)
Kochia (Kochia scoparia L. Schrad.), one of the most problematic weeds in the Great Plains of United States, has evolved resistance to some herbicides including glyphosate (5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) inhibitor) which was first reported in western Kansas in 2007. The objectives of this research were to (1) characterize six kochia populations from western Kansas on the basis of glyphosate resistance or multiple herbicide resistance, (2) determine germination characteristics of the populations and evaluate their growth and fecundity in the field, and (3) determine if EPSPS gene amplification responsible for glyphosate resistance in kochia was associated with growth and fecundity cost in the plants. Six kochia populations were from Scott, Finney, Thomas, Phillips, Wallace, and Wichita counties. Based on shikimate assay for glyphosate and recommended field rates for four tested herbicides, three kochia populations (Scott (SC-R), Finney (FN-R), and Thomas (TH-R)) were grouped into glyphosate-resistant (GR) and three populations (Phillips (PH-S), Wallace (WA-S) and Wichita (WI-S)) were grouped into glyphosate-susceptible (GS). All populations were resistant to dicamba (synthetic auxin) and chlorsulfuron (acetolactate synthase inhibitor), however, atrazine (PS II inhibitor) resistance in FN-R was noted as exceptional among the GR populations. Across the three germination temperatures (5, 10 and 15 C), the GR populations consistently had less total cumulative germination and at 15 C, they consistently required more time to attain 50% of maximum cumulative germination than the GS populations. Both the field study and evaluation of relationship between EPSPS gene amplification and plant performance showed that differences in plant height, biomass accumulation and fecundity among populations were not in respect to glyphosate resistance but rather, differences in their inherent ability to grow and produce seeds in the presence or absence of neighbors. This research suggests that fitness differences between GR and GS kochia populations could be identified in germination characteristics but not in their growth or fecundity.
Keywords: Ecological fitness; Glyphosate resistant weed; Kochia; Seed germination; Growth; Enolpyruvylshikimate-3-phosphate synthase